Anthropic cut marks in extinct megafauna bones from the Pampean region (Argentina) at the last glacial maximum - del Papa, Mariano Carlos (2024)
The initial peopling of South America is a topic of intense archaeological debate. Among the most contentious issues remain the nature of the human-megafauna interaction and the possible role of humans, along with climatic change, in the extinction of several megamammal genera at the end of the Pleistocene. In this study, we present the analysis of fossil remains with cutmarks belonging to a specimen of Neosclerocalyptus (Xenarthra, Glyptodontidae), found on the banks of the Reconquista River, northeast of the Pampean region (Argentina), whose AMS 14C dating corresponds to the Last Glacial Maximum (21,090–20,811 cal YBP). Paleoenvironmental reconstructions, stratigraphic descriptions, absolute chronological dating of bone materials, and deposits suggest a relatively rapid burial event of the bone assemblage in a semi-dry climate during a wet season. Quantitative and qualitative analyses of the cut marks, reconstruction of butchering sequences, and assessments of the possible agents involved in the observed bone surface modifications indicate anthropic activities. Our results provide new elements for discussing the earliest peopling of southern South America and specifically for the interaction between humans and local megafauna in the Pampean region during the Last Glacial Maximum.